2006
DOI: 10.1152/ajplung.00463.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of regional cellular responses to local mechanical stress in acute lung injury

Abstract: -Human acute lung injury is characterized by heterogeneous tissue involvement, leading to the potential for extremes of mechanical stress and tissue injury when mechanical ventilation, required to support critically ill patients, is employed. Our goal was to establish whether regional cellular responses to these disparate local mechanical conditions could be determined as a novel approach toward understanding the mechanism of development of ventilator-associated lung injury. We utilized cross-species genomic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 59 publications
5
60
0
1
Order By: Relevance
“…Although the animals remain viable after ventilation at 80% TLC or higher, we have observed that prolonged ventilation (e.g., > 2 h) at higher volumes (80-100% TLC) results in hemorrhage and damage of the lung epithelium (data not shown), as has previously been shown by a number of labs (40)(41)(42)(43). However, at lower volumes, even for these extended periods of time, no damage was seen.…”
Section: Discussionsupporting
confidence: 76%
“…Although the animals remain viable after ventilation at 80% TLC or higher, we have observed that prolonged ventilation (e.g., > 2 h) at higher volumes (80-100% TLC) results in hemorrhage and damage of the lung epithelium (data not shown), as has previously been shown by a number of labs (40)(41)(42)(43). However, at lower volumes, even for these extended periods of time, no damage was seen.…”
Section: Discussionsupporting
confidence: 76%
“…7 Identified SD for control kidney ( ϭ 0.274) and lung ( ϭ 0.271) tissues were submitted to the microarray sample size identifying formula 40 with power (1 Ϫ ␤) ϭ 90% and 1% FDR (significance level ␣ ϭ 0.01) for kidney and 2% for more heterogeneous lung tissue. 41 The power.t.test function of R2.3.1 program (www.r-project.org) identified fold change for kidney log 2 (⌬) ϭ 1.513 (numerical 2.85) and lung log 2 (⌬) ϭ 1.249 (numerical 2.38).…”
Section: Statistical and Power Prediction For Minimum Array Requiremementioning
confidence: 99%
“…Alternatively, a separate internal or mitochondrial pathway can mediate apoptosis via cytochrome c and caspase activation. Lung tissue from both humans with ALI and animal models of ALI demonstrate activation of apoptotic pathways in the alveolar epithelium [22,23]. Matute-Bello and colleagues reported that bronchoalveolar fluid from patients with ALI contained soluble Fas ligand (sFasL), and the concentration of sFasL at the onset of ARDS was significantly higher in patients who died [24].…”
Section: Alveolar Epithelial Cell Apoptosismentioning
confidence: 99%